STRATEGI PENANGANAN ANAK PUTUS SEKOLAH PADA SUKU BAJO MELALUI OPTIMALISASI PERAN KOMITE SEKOLAH DI KECAMATAN TIWORO KABUPATEN MUNA - La Manguntara; La Iba (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2015)
The objectives of this study are to formulate and to implement the handling model of school dropouts through optimization of the role (empowerment) of School Committee, so that the children dropped out from school in the Tiworo District of Muna Regency could back to school. This study used a qualitative approach. The focus of research is geared to describe and to analyze: a) the dropout rate and the contributing factors; b) the perception of parents and dropouts student on the importance of education; c) The efforts undertaken by the School Committee, Ministry of Education in districts and other stakeholders to address the problem of child. The data was collected through in-depth interviews (depth interview), documentation (documentation), and observations (observation). The results showed that the numbers of school dropouts are caused by two main factors, namely internal factors and external factors. Internal factors related to the low interest and motivation of children for school as well as their erroneous perception of the meaning of education. External factors are closely related to the problem of parents’ job as traditional fishermen. Efforts are being made to deal with dropouts so far not been seriously implemented and coordinated. The effort done was limited to what was done by the parents to encourage their children for returning to school (for a small number of parents). The government looks the phenomenon of school dropouts in this area as only a problem of lack of educational facilities that are inadequate, so the solution among others is by building the junior high school (now in the process of completion). While factors erroneous perception of parents and children dropping out of school as a cause of many school dropouts seems to escape the attention of the government. Keywords: strategy, school dropouts’ children, optimization, school committee